DOI: 10.18297/etd/700
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of intake and disposition decisions by child protective services professionals.

Abstract: This study examined intake and post-investigative disposition decision making among professionals engaged in child protective services to understand disproportionality and disparities in the child welfare system. Using child welfare, decision making, and attribution theories as a framework, a multivariate 2x2x2 factorial vignette design was used to examine intake and post-investigative disposition decision making among 400 child protective caseworkers and supervisors employed in a Midwestern state. Data were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…For example, trained social workers made decisions similar to colleagues educated in different fields (Howell, 2008). In another study by Johnson (2010), respondents' educational level as well as attitudes towards race, poverty and family structure varied, but no significant differences were found in intake decision‐making. Similar results were seen in McCormack et al (2020).…”
Section: Decision‐making Ecology Themesmentioning
confidence: 93%
See 4 more Smart Citations
“…For example, trained social workers made decisions similar to colleagues educated in different fields (Howell, 2008). In another study by Johnson (2010), respondents' educational level as well as attitudes towards race, poverty and family structure varied, but no significant differences were found in intake decision‐making. Similar results were seen in McCormack et al (2020).…”
Section: Decision‐making Ecology Themesmentioning
confidence: 93%
“…In addition, other vignette‐based studies indicate that signs of domestic violence (i.e. bruises) are viewed as a serious risk factor (Skiveness & Stenberg, 2015) and associated with the decision to screen‐in the case (Johnson, 2010). Analysing state‐level CPS data and population‐based data in the USA, Fisher et al (2019) concluded that children with autism spectrum disorders (ASDs) were less likely than children without ASDs to have referrals screened in for further action (62% vs. 91.6%, respectively).…”
Section: Decision‐making Ecology Themesmentioning
confidence: 99%
See 3 more Smart Citations